-(x+9)=

Simple and best practice solution for -(x+9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(x+9)= equation:


Simplifying
-1(x + 9) = 0

Reorder the terms:
-1(9 + x) = 0
(9 * -1 + x * -1) = 0
(-9 + -1x) = 0

Solving
-9 + -1x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + -1x = 0 + 9

Combine like terms: -9 + 9 = 0
0 + -1x = 0 + 9
-1x = 0 + 9

Combine like terms: 0 + 9 = 9
-1x = 9

Divide each side by '-1'.
x = -9

Simplifying
x = -9

See similar equations:

| 5x=28+3x | | 6x+2y-3x+7y= | | -2c(8c-7)(c+5)=0 | | X^2-y=0.75 | | y=(4x-1)ln(5x-1) | | [6/2]-[3x0]= | | -6(x+2)=9x-3 | | p^6-52p^4+640p^2-1024=0 | | 3(1-2x)+7= | | Y=-3x+180 | | 2p+3q+5r+7= | | -0.5x+0y=14 | | -7t+11=-73 | | (v^2-9v+18)(3v+27)=0 | | -18=8x-9x-5x | | w^2-w-18=0 | | 0=10t^2+25t-30 | | Ln(x+1)=0.43 | | 30x+20y=248 | | y+5x+13= | | ((ln)x)=10 | | ln(1-4k)=8k | | xy+x+y=23 | | tan(2x)=cos(x) | | -2[5-(5-4s)]+4=-3s | | 3x+4-2=9.5 | | 10-p=4p-12 | | 5(ln(x)/ln(7))-(ln(49x)/ln(7))=-2 | | -9(2+A)+4(2A+9)=1 | | 21x+3y-48=0 | | (7-2i)/(3-4i) | | 7y-8=y+4 |

Equations solver categories